Impact of Grilling Meat or Fish at Home on Peak Expiratory Flow Rate in Adults With Asthma - Lee, Hyun (Allergy Asthma Immunol Res, 2020)
Grilling, a common cooking method worldwide, can produce more toxic gases than other cooking methods. However, the impact of frequently grilling meat or fish at home on airflow limitation in adult asthma has not been well elucidated. We performed a prospective cohort study of 91 adult patients with asthma enrolled from 2 university hospitals. Of the patients, 39 (42.9%) grilled meat or fish at least once a week and 52 (57.1%) less than once a week. Patients who grilled at least once a week tended to have lower peak expiratory flow rate (PEFR) than those who grilled less than once a week (median, 345.5 L/min; 95% confidence interval [CI], 291.8–423.2 L/min vs. median, 375.1 L/min; 95% CI, 319.7–485.7 L/min; P = 0.059). Among patients with severe asthma who received step 4-5 treatment, PEFR was significantly lower in patients who grilled at least once a week compared with those who grilled less than once a week (median, 297.8 L/min; 95% CI, 211.3–357.7 L/min vs. median, 396.1 L/min; 95% CI, 355.0–489.6 L/min; P < 0.001). Our results suggest that the frequency of grilling meat or fish at home may affect PEFR in asthmatic patients, especially those with severe asthma who needed a high level of asthma treatment.